2016
DOI: 10.1002/dmrr.2806
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic volume is reduced in patients with latent autoimmune diabetes in adults

Abstract: Aims This study aimed to compare pancreatic volume and its clinical significance among patients with type 2 diabetes mellitus (DM), adult-onset type 1 DM and latent autoimmune diabetes in adults (LADA).Methods This is a cross-sectional study. One hundred twenty-six outpatients (68 with LADA and 58 with type 1 DM) and 158 inpatients (71 with type 2 DM and 87 non-diabetic controls) were recruited during May-July 2013 in Shanghai Jiao Tong University Affiliated Sixth People's Hospital. All the patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
2
10
0
2
Order By: Relevance
“…Only a few studies to date have examined PV in patients with slowly progressive type 1 diabetes or latent autoimmune diabetes in adults. The PVI reduction in the current study was comparable between acute‐onset type 1 diabetes and slowly progressive type 1 diabetes.…”
Section: Discussionsupporting
confidence: 57%
“…Only a few studies to date have examined PV in patients with slowly progressive type 1 diabetes or latent autoimmune diabetes in adults. The PVI reduction in the current study was comparable between acute‐onset type 1 diabetes and slowly progressive type 1 diabetes.…”
Section: Discussionsupporting
confidence: 57%
“…Compared to age-matched controls, the weight of postmortem T1D pancreata is reduced by 35-45% (6,20,22,33). Imaging studies of those living with T1D have demonstrated that the volume of the pancreas is reduced 18-52% compared to controls depending on method (i.e., ultrasound, computerized tomography (CT), or magnetic resonance imaging (MRI) (5,7,9,13,15,21,24,28,31,32). These data provide strong evidence to support the hypothesis that T1D is not just a disease of the endocrine compartment, but also affects the pancreas at large.…”
Section: The Exocrine Pancreas In Patients With Diabetesmentioning
confidence: 99%
“…不论是在临床或是科研工作中, LADA患者的自 身免疫攻击和胰岛素分泌水平进行性降低一直是人们 关注的焦点, 但LADA患者中胰岛素敏感性和胰岛素 抵抗的研究却很少. Carlsson等人 [34] 在对LADA胰岛β 细胞分泌胰岛素功能和胰岛素敏感性的研究中发现, LADA患者在精氨酸刺激下的胰岛素分泌能力较 T2DM差, 而胰岛素的敏感性在LADA与T2DM中均有 受损, 且两者之间并无统计学差异, 由此可知LADA兼 具经典T1DM的胰岛素分泌障碍和2型糖尿病胰岛素 抵抗的特点 [35,36] . 本研究组 [37] 亦曾利用稳态模型评估 (homeostasis model assessment, HOMA) LADA患者中 GADA与胰岛素抵抗的关系, 进一步发现低GADA滴 度患者相较高滴度者胰岛素抵抗更为严重.…”
Section: Lada患者的代谢特征unclassified